P247 Can text messages increase safer sex behaviours in young people: intervention development and pilot randomised controlled trial. (30th June 2016) - Free, Caroline; McCarthy, Ona; Baraitser, Paula; French, Rebecca; Wellings, Kaye; Devries, Karen; Rathod, Sujit; Michie, Susan; Hart, Graham; Bailey, Julia
Abstract : Background/introduction: Younger people bear the heaviest burden of sexually transmitted infections (STIs). The acceptability and feasibility of conducting a randomised controlled trial of safer sex support delivered by text message are not known. Aim(s)/objectives: To develop a safer sex intervention delivered by text messages for people aged 16–24. To assess the acceptability and feasibility of a randomised controlled trial. Methods: The intervention was developed based on evidence, behavioural theory, and user views. It was designed to reduce STIs by increasing correct treatment of STI, partner notification, condom use and STI testing. We conducted a pilot, randomised controlled trial with people aged 16–24 diagnosed with chlamydia or reporting unprotected sex with more than one partner in the last year. We conducted qualitative interviews. Results: Two hundred participants were randomised. We fully recruited early and achieved 81% follow up for our proposed primary outcome cumulative incidence of chlamydia at 12 months. Ninety-seven percent of messages sent were successfully delivered to participants' phones. Recipients reported that the tone, language, content, and frequency of messages was appropriate. Messages reportedly increased knowledge and confidence in how to use and negotiate condom use, and reduced stigma enabling participants to tell a partner about a STI. Discussion/conclusion: T he intervention is acceptable and a main trial is feasible. The NIHR have funded a randomised controlled trial to establish the effects of the intervention on sexually transmitted infections at 12 months.